Kosovar Muslims and the Hanafi School: Legal Interpretations in a Post-Ottoman Context - Mimoza Hatixhe; Sofija Hatice Petrović; Selma Nikolić; Katarina Snežana Ljiljana (Indonesian Journal of Islamic Law, 2025)
This article explores the enduring influence of the Hanafi school of Islamic jurisprudence among Kosovar Muslims in the post-Ottoman era, focusing on its legal interpretations and social implications. The study examines how the Hanafi tradition, which was institutionalized during Ottoman rule, has shaped legal practices and community norms in Kosovo amidst socio-political transformations, including the transition to a secular legal framework. Drawing on historical analysis, legal documents, and interviews with religious scholars, this research investigates the application of Hanafi jurisprudence in areas such as marriage, inheritance, and community dispute resolution. The findings reveal a dynamic interplay between adherence to traditional Hanafi principles and adaptations to modern legal and societal contexts. While the Hanafi framework remains a cornerstone of religious identity and practice, contemporary challenges—such as legal pluralism, secular governance, and globalization—have prompted nuanced reinterpretations to align with the changing needs of the Muslim community in Kosovo. This study underscores the role of Islamic jurisprudence in shaping communal and individual identities in a post-Ottoman context. It highlights the resilience and adaptability of the Hanafi school while contributing to broader discussions on integrating Islamic traditions within modern legal systems. The article concludes by emphasizing the importance of localized approaches to Islamic jurisprudence that respect historical legacies while addressing contemporary realities.